Bullying, peer harassment, and victimization in the schools : the next generation of prevention - Elias, Maurice J.; Zins, Joseph E. (Haworth Press, 2003)
Presents an analysis of research on harassment, bullying, and victimization, and documents this type of harassment both inside and outside the United States.